Radar Systems for Ice and Snow Measurements Onboard Manned and Unmanned Aircraft - Rodriguez-Morales, F.; Gomez-Garcia, D.; Arnold, E.; Hale, R.; Keshmiri, S.; Leuschen, C.; Li, J.; Paden, J.; Cardenas Mansilla, Carlos Alberto (My University, 2018)
In this paper, we present a brief overview of the state of the art in radar systems for ice and snow measurements. Emphasis is given to the instrumentation developed at the University of Kansas for multi-band data retrieval at frequencies ranging from 14 MHz to 38 GHz, which is operated onboard manned and unmanned aircraft. The information collected with these systems is used to estimate parameters such as ice thickness, ice surface and bedrock topography, snow cover thickness on sea ice, and annual snow accumulation. We give a summary of recent field programs (including operations out of Punta Arenas, Chile), present sample results, and discuss recent collaborations with Chilean institutions.
Keywords: radio echo sounding; airborne radar; cryospheric remote sensing